Cyber security of industrial control systems in the future internet environment - Stojanović, Mirjana D.; Bostjancic Rakas, Slavica V. 1978 (Advances in Information Security, Privacy, and Ethics (AISPE) book series, 2020)
""This book provides research on current security risks in critical infrastructure schemes with the implementation of information and communication technologies. While highlighting topics such as intrusion detection systems, forensic challenges, and smart grids, this publication explores specific security solutions within industrial sectors that have begun applying internet technologies to their current methods of operation"--Provided by publisher"--